Vitamin D Status in Women with Uterine Fibroids: A Cross-sectional Study - Farzaneh, Farah; Sadeghi, Kiana; Chehrazi, Mohammad (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Uterine fibroids (UFs) affect women of reproductive age and lead to major morbidity in premenopausal women. Identifying modifiable risk factors could help develop new UF prevention and treatment strategies. OBJECTIVES: The purpose of this research was to investigate the relationship between serum Vitamin D3 levels and UF in women seeking gynecological services. METHODS: This case–control design was conducted in September 2018 at the outpatient gynecology clinic of Shahid Beheshti University of Medical Sciences, Tehran, Iran. Cases had at least one ultrasound confirmed fibroid lesion with an average volume of 2 cm or greater. The outpatient clinic has enrolled a control group of patients without UF, based on transvaginal ultrasonography or any other gynecologic pathology. Radioimmunoassay techniques were applied to measure serum Vitamin D [25(OH) D3] levels. RESULTS: A total of 148 patients met inclusion criteria, 71 women were had at least one UF and the remaining 77 participants showed normal, UF-free uterine structure. The mean serum concentration of 25-hydroxyvitamin D3 was lower in UF patients (21.37 ± 7.49 ng/mL) than without (24.62 ± 9.21 ng/mL) (p = 0.02). A modified odds ratio derived from a backward logistic regression model for 25-hydroxyvitamin D3 that included positive family history, age, body mass index, bleeding volume, physical activity, sun exposure, and history of abortion was 0.92 (95% CI, 0.88–0.98) (P = 0.02). CONCLUSION: For women with UFs, the serum level of 25-hydroxyvitamin D3 was significantly lower than in controls. Vitamin D3 deficiency is a potential risk factor for UFs to occur.